Robust Resource Allocation in Future Wireless Networks - Parsaeefard, Saeedeh; Sharafat, Ahmad Reza.; Mokari, Nader; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book presents state-of-the-art research on robust resource allocation in current and future wireless networks. The authors describe the nominal resource allocation problems in wireless networks and explain why introducing robustness in such networks is desirable. Then, depending on the objectives of the problem, namely maximizing the social utility or the per-user utility, cooperative or competitive approaches are explained and their corresponding robust problems are considered in detail. For each approach, the costs and benefits of robust schemes are discussed and the algorithms for reducing their costs and improving their benefits are presented. Considering the fact that such problems are inherently non-convex and intractable, a taxonomy of different relaxation techniques is presented, and applications of such techniques are shown via several examples throughout the book. Finally, the authors argue that resource allocation continues to be an important issue in future wireless networks, and propose specific problems for future research.
Chapter 1. Introduction -- Chapter 2.Robust Cooperative Resource Allocation -- Chapter 3. Robust Non-Cooperative Resource Allocation -- Chapter 4.Non-Convex Robust Problems -- Chapter 5.Conclusions and Future Research.
Keywords: Telecommunication; Computer networks .; Communications Engineering, Networks; Computer Communication Networks